2020
DOI: 10.3389/fchem.2020.00034
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol: An Optimal Hydrogen Source for Microwave-Promoted Cu-Catalyzed Transfer Hydrogenation of Nitrobenzene to Aniline

Abstract: The search for sustainable alternatives for use in chemical synthesis and catalysis has found an ally in non-conventional energy sources and widely available green solvents. The use of glycerol, an abundant natural solvent, as an excellent "sacrificial" hydrogen source for the copper-catalyzed microwave (MW)-promoted transfer hydrogenation of nitrobenzene to aniline has been investigated in this work. Copper nanoparticles (CuNPs) were prepared in glycerol and the efficacy of the glycerol layer in mediating the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…The use of MW irradiation (Milestone MicroSynth, constant power: 120 W) greatly improved reaction performance, and 90 min were sufficient for reaction completion. As already observed in our previous studies, simultaneous irradiation with MW (2.45 GHz, 90 W) and US (20.3 kHz, 40 W) is able to enhance heat and the mass transfer, as well as catalyst deagglomeration, leading to improved reaction rate and selectivity [22a] . US significantly influenced Cu(0) nanoparticles with smaller size and narrower particle size distribution.…”
Section: Resultssupporting
confidence: 77%
“…The use of MW irradiation (Milestone MicroSynth, constant power: 120 W) greatly improved reaction performance, and 90 min were sufficient for reaction completion. As already observed in our previous studies, simultaneous irradiation with MW (2.45 GHz, 90 W) and US (20.3 kHz, 40 W) is able to enhance heat and the mass transfer, as well as catalyst deagglomeration, leading to improved reaction rate and selectivity [22a] . US significantly influenced Cu(0) nanoparticles with smaller size and narrower particle size distribution.…”
Section: Resultssupporting
confidence: 77%
“…Reduction by transfer hydrogenation has addressed this limitation, and recently, an example of the copper-catalyzed (Cu(0) nanoparticles) reduction of nitrobenzene in glycerol was described in MW large batch mode ( Scheme 10 ). 70 Because glycerol is a biobased and eco-friendly solvent with a high MW adsorption capacity and a low vapor pressure, and because the reaction demanded a high temperature, a large-scale synthesis of the MW batch mode was studied. The reaction was performed on an almost 1 L scale in a pilot MW reactor in 95% yield, and the study demonstrated that the sample temperature in the reaction mixture was between 130 and 115 °C, with a high absorbance of delivered MW power when the power was maintained constant ( Figure 5 ).…”
Section: Applied Homogeneous and Heterogenoeus Catalysismentioning
confidence: 99%
“…It appears that the glycerol conversion increases significantly with the increase in NiO loading level and MAC power. In this reaction, glycerol also acts as an excellent “sacrificial” hydrogen source [ 47 ]. Additional nickel content on the zeolite support surface can improve the catalytic activity at the lower reaction temperature.…”
Section: Resultsmentioning
confidence: 99%